4a-5c+3a-c=

Simple and best practice solution for 4a-5c+3a-c= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4a-5c+3a-c= equation:


Simplifying
4a + -5c + 3a + -1c = 0

Reorder the terms:
4a + 3a + -5c + -1c = 0

Combine like terms: 4a + 3a = 7a
7a + -5c + -1c = 0

Combine like terms: -5c + -1c = -6c
7a + -6c = 0

Solving
7a + -6c = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '6c' to each side of the equation.
7a + -6c + 6c = 0 + 6c

Combine like terms: -6c + 6c = 0
7a + 0 = 0 + 6c
7a = 0 + 6c
Remove the zero:
7a = 6c

Divide each side by '7'.
a = 0.8571428571c

Simplifying
a = 0.8571428571c

See similar equations:

| 2a+3x-4x-5a= | | 9+b=c+3a | | -2(x-1)=-2x-(x+4) | | 9x-11-2x+4= | | x^2+y^2-12y=0 | | 2-10=z/-7 | | 3x-5y+4y+2x= | | 14x^2-24=0 | | 0=X^4-8x | | y-.333=2.66 | | -3(x-2)+4(x-7)=20 | | u+.333=.333 | | 4x+4(6x+3)= | | -0.55p-5=0.45 | | cosx/2-1=0 | | 7x^4+2x^2+21=0 | | -4-(2y-1)=-(3y+1) | | 21/4=8/t | | 4*(x+6)= | | X(-2)+18=50(-3x)+25 | | 2*(x+3)= | | 2*(3a)= | | -24+x=36 | | (-2x)+5+3x+-4x+(-1)+(-x)= | | 2x+(-2)=17 | | 6*2s=39 | | ×/3-4=×/5-6 | | 2(-1)+y=17 | | Y+12=c | | 3/7=n/21 | | 4.5+x=-2.3 | | 10x-15=6x+14 |

Equations solver categories